INVESTMENTS: AN ANALYSIS OF THE KNOWLEDGE OF UNDERGRADUATE BUSINESS STUDENTS AT THE UNIVERSIDADE EVANGÉLICA DE GOIÁS – CAMPUS CERES (CIPEEX, 2024)
IN ORDER TO DEMYSTIFY THE INTRINSIC RELATIONSHIP BETWEEN HUMAN FINANCIAL BEHAVIOR AND THE IMPORTANCE OF FINANCIAL EDUCATION (FE), THIS STUDY FOCUSES ON ANALYZING STUDENTS' KNOWLEDGE OF INVESTMENTS BY APPLYING A QUESTIONNAIRE. THE UNDERSTANDING OF HUMAN FINANCIAL BEHAVIOR, HIGHLIGHTED BY STUDIES IN BEHAVIORAL FINANCE, REVEALS PEOPLE'S TENDENCY TO BE MORE IMPACTED BY LOSSES THAN GAINS. THE IMPORTANCE OF FE IS HIGHLIGHTED, EMPHASIZING THAT NOT EVERY INVESTOR IS RATIONAL. DESPITE THE NEED FOR FINANCIAL PLANNING TO ACHIEVE GOALS, IT IS CRUCIAL TO ASSESS THE CURRENT SITUATION THAT INFLUENCES FINANCIAL DEVELOPMENT AND THE RELEVANCE OF ACQUIRING INVESTMENT KNOWLEDGE GOES BEYOND FINANCIAL MANAGEMENT, ENCOMPASSING INFORMED AND COHERENT DECISION-MAKING SKILLS. THE INVESTOR'S PROFILE, WHETHER CONSERVATIVE, MODERATE OR BOLD, INFLUENCES CHOICES, AND THEY ARE RISK-AVERSE TO VARYING DEGREES. HOWEVER, IN BEHAVIORAL FINANCE, BIASES SUCH AS LOSS AVERSION, ANCHORING AND OVERCONFIDENCE IMPACT DECISIONS. IN THIS WAY, THE STUDY SEEKS TO ANALYZE THE INVESTMENT KNOWLEDGE OF BUSINESS ADMINISTRATION STUDENTS AT THE UNIVERSIDADE EVANGÉLICA DE GOIÁS - CAMPUS CERES, ASSESSING THE RELEVANCE AND IMPORTANCE OF FE FOR THE GROUP SURVEYED AND IDENTIFYING THE MAIN TYPES OF INVESTMENTS ACCEPTED. THE FIELD RESEARCH ADOPTS A BIBLIOGRAPHIC THEORETICAL FOUNDATION, ANALYZING AND SYNTHESIZING INFORMATION CONTAINED IN DOCUMENTS ALREADY PUBLISHED, IN AN EXPLORATORY WAY CONSIDERING INVESTIGATING A PARTICULAR PROBLEM, WITH A CROSS-SECTIONAL FORM EXAMINING A SPECIFIC POINT IN A GIVEN POPULATION AND QUANTITATIVE COLLECTING DATA TO DESCRIBE AND STATISTICALLY EXPLORE THE VARIABLES, INVOLVING THE APPLICATION OF A 19-QUESTION QUESTIONNAIRE APPROVED BY THE CEP OF UNIEVANGÉLICA UNDER OPINION NUMBER: 6. 268.039, AND FOCUSES ON A POPULATION OF 77 STUDENTS DISTRIBUTED OVER VARIOUS PERIODS OF THE COURSE, WITH A RECOMMENDED PARTICIPATION OF AT LEAST 63 STUDENTS TO ACHIEVE A 95% CONFIDENCE LEVEL, ACCORDING TO AN ESTIMATE OBTAINED USING THE RAOSOFT® PLATFORM. THE RESULTS AIM TO PROVIDE A COMPREHENSIVE VIEW OF THE STUDENTS' INVESTMENT KNOWLEDGE, IDENTIFYING COMMON CHARACTERISTICS AMONG THOSE WITH EXPERIENCE IN THE FIELD. IT ALSO AIMS TO ASSESS THE RELATIONSHIP BETWEEN THE PROPENSITY TO INVEST AND THE MATURITY OF UNIVERSITY BUSINESS STUDENTS. IN GENERAL, THE RESEARCH WILL CONTRIBUTE TO UNDERSTANDING THE LEVEL OF KNOWLEDGE AND APPLICABILITY OF THE DISCIPLINES, MAKING IT POSSIBLE TO UNDERSTAND COMMON CHARACTERISTICS AMONG STUDENTS.
Keywords: Financial Education; Higher Education; Investment; Investor Profile